A survey of root-knot and false root-knot nematodes at commercial vegetable farms under protected cultivation in La Plata Green Belt, Argentina - Rusconi, Jose Matias; Nico, Andrés; Salas, Augusto; Iglesias, Rosario; Ibáñez Shimabukuro, Marina; Moncada, Melisa; Achinelly, María Fernanda (Brill, 2025)
Root-knot and false root-knot nematodes, Meloidogyne spp. and Nacobbus spp., respectively, represent one of the most economically-impacting crop protection concerns at La Plata Green Belt (LPGB), Argentina. The aims of this paper were to determine the frequency and distribution of root-knot and false root-knot nematodes under protected cultivation and an update of the recorded area of LPGB. An exhaustive survey of these nematodes was carried out. A total of 75 samples, corresponding to an equivalent number of prospected areas, were taken. Eleven of the prospected squares (14.6% of the total) were free of galling nematodes; coincidently, these were areas recently incorporated into protected horticulture. The other remaining areas were positive for the presence of galling nematodes. Nacobbus spp. were found in 93.4% of the positive samples, whereas Meloidogyne spp. were found in 12.5%. In three out of 75 samples co-infestation by both Nacobbus and Meloidogyne was registered. Solanaceae and Amaranthaceae were the most frequent hosts for both genera of galling nematodes. Two populations of N. celatus from tomato and pepper, respectively, were identified by the mitochondrial gene CoxI. A first molecular analysis of M. arenaria for the LPGB is reported here.